2004
DOI: 10.1177/0305735604041494
|View full text |Cite
|
Sign up to set email alerts
|

Graphic Representations of Short Musical Compositions

Abstract: A B S T R AC T Sixty college students were asked to 'make any marks' to visually represent five short orchestral compositions, and to write essays to explain their graphic representations. Most musically trained participants provided abstract representations (symbols or lines), while most pictorial representations (images or pictures telling a story) were created by musically untrained participants. A content analysis of the essays revealed that trained participants focused on themes, repetition, mode, changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 28 publications
2
50
0
8
Order By: Relevance
“…The musically trained participants demonstrated a tendency to create representations aligned on an x-y axis (henceforth referred to as Cartesian), representing time in a horizontal, left-to-right fashion, and depicting aspects of the musical surface (primarily pitch) on the vertical axis, in accordance with findings described elsewhere (Athanasopoulos & Moran, 2012;Athanasopoulos, Moran, & Frith, 2011). However, Tan and Kelly (2004) also found that musically untrained participants tended to provide pictorial representations through images or pictures telling a story. Küssner (2013) obtained comparable results from British participants.…”
Section: Music and Shapementioning
confidence: 97%
See 3 more Smart Citations
“…The musically trained participants demonstrated a tendency to create representations aligned on an x-y axis (henceforth referred to as Cartesian), representing time in a horizontal, left-to-right fashion, and depicting aspects of the musical surface (primarily pitch) on the vertical axis, in accordance with findings described elsewhere (Athanasopoulos & Moran, 2012;Athanasopoulos, Moran, & Frith, 2011). However, Tan and Kelly (2004) also found that musically untrained participants tended to provide pictorial representations through images or pictures telling a story. Küssner (2013) obtained comparable results from British participants.…”
Section: Music and Shapementioning
confidence: 97%
“…Undertaking just this task, Tan and Kelly (2004) used whole musical compositions as stimuli, requesting musically trained and untrained US college participants to "make any marks" in order to represent the sounds visually. The musically trained participants demonstrated a tendency to create representations aligned on an x-y axis (henceforth referred to as Cartesian), representing time in a horizontal, left-to-right fashion, and depicting aspects of the musical surface (primarily pitch) on the vertical axis, in accordance with findings described elsewhere (Athanasopoulos & Moran, 2012;Athanasopoulos, Moran, & Frith, 2011).…”
Section: Music and Shapementioning
confidence: 99%
See 2 more Smart Citations
“…This issue has been addressed by scholars from various disciplines to shed light on questions such as how we perceive motion in music (Repp, 1993;Godøy, Haga & Jensenius, 2006), how auditory information is processed and mapped onto the visual domain (Marks, 2004;Spence, 2011), how children develop an understanding of rhythm (Bamberger, 1995) and represent music graphically (Reybrouck, Verschaffel, & Lauwerier, 2009;Verschaffel, Reybrouck, Janssens, & Van Dooren, 2010), and how musical training influences the ways in which we represent short but complete musical compositions visually (Tan & Kelly, 2004). The idea that musical training affects how adults hear music has been around for several decades (Sloboda, 1985), including the belief that experts and novices listen to music differently (Gromko, 1993) and that musical training leads to adults paying more attention to the structural properties of musical stimuli that they hear (Sloboda, 1984).…”
Section: Background and Motivationmentioning
confidence: 99%